(untitled) (American International Journal of Supply Chain Management, 2024)
The heightening of competition and the quest for market share has left business persons and research communities re-examining methods that worked well in the past and reinventing a new combination of competitive practices. This paper examines supply chain quality management practices vis-à-vis Porter’s generic strategies in terms of their ability in building the competitive power of manufacturing companies in Cameroon. The study makes use of quantitative approach, surveying 900 actors involved in the supply chains of 20 manufacturing companies in Cameroon through convenience sampling. Primary data was captured through the administration of a five-point Likert scale questionnaire. The data were analysed using three multiple regression models. The results show that supply chain quality management accounts for 51.3% of variations in the marketing performance while Porter’s generic strategies accounted for 2% of variations in the marketing performance of the companies. The findings of this study suggest that supply chain quality management is a better tool for influencing the marketing performance of manufacturing companies in Cameroon over Porter’s generic strategies and hence building the competitive power of the companies at all levels of the study. JEL Classification Code: M31.